Mechanistic insights toward progress in alogliptin beyond glycemic control: translational perspective - Faraha Ahmed; Syed Sufian Ahmad; M. Mumtaz Alam; M. Shaqiquzzaman; Abul Kalam Najmi; Mohammad Ahmed Khan (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Alogliptin belongs to gliptin family of drugs that inhibits ubiquitous enzyme dipeptidyl peptidase-4 (DPP-4). Gliptins increase the life-span of incretin hormones that appear to benefit functioning of several organs via various signaling pathways. Main body Alogliptin is approved for treatment of type 2 diabetes mellitus (T2DM) in majority of the countries. It is administered orally and efficacious as monotherapy as well as combined therapy with other T2DM drugs, such as pioglitazone and metformin. It has a good safety profile, well-tolerated in elderly patients and in patients with co-morbid conditions including risks of cardiovascular event, renal or hepatic insufficiency. Therefore, alogliptin is incessantly experimented and investigated for its therapeutic benefit. Recent developments have indicated potential of alogliptin in discrete pathological conditions. Emerging evidences suggest prominent cardioprotective, hepatoprotective, reno-protective, anti-inflammatory and lipid-lowering capacity of alogliptin. Apart from inhibiting DPP-4 enzyme, alogliptin also affects several signaling mechanisms to exhibit protective effects in patients with diabetes-induced complications. Conclusion This review highlights the potential role of alogliptin and mechanisms involved in amelioration of several other pathological conditions apart from its role in glucose metabolism. Thus, this may provide insights for better utilization and repurposing of alogliptin as a therapeutic agent.